转向节特性对盘式制动器尖叫影响的研究 - 金鑫君; 方晓汾; 邓小雷 (Jixie qiangdu)
Considering that the effect of steering knuckle on squeal is usually ignored when performing analysis of disc brake squeal,in this work,a finite element model of disc brake system including steering knuckle component is established,and the vibration characteristics of the brake system are predicted and analyzed by using complex eigenvalue analysis method.On this basis,the influence of steering knuckle characteristics on brake squeal instability behavior is studied.The results show that the increase of friction coefficient will enhance the tendency of braking system to generate squeal instability,and the steering knuckle plays a significant role in affecting the coupling between different components of the brake system.The mode of knuckle may induce the generation of brake squeal.Ignoring the steering knuckle during squeal analysis and prediction will cause the phenomenon of‘over-prediction’and ‘under-prediction’.The stiffness of steering knuckle has a strong influence on squeal behavior.The increase of steering knuckle stiffness will cause more unstable vibration of frequency and accordingly increase the squeal intensity of the system.In addition,since there is no significant friction movement between the knuckle and the disc hub,the friction coefficient at the knuckle-disc hub connection shows little impact on the braking squeal behavior of the system.The above research results provide a basis for understanding the generation of brake squeal and proposing reasonable measures to improve the squeal.